Transgresywne wahadełko poezji Bogdana Loebla - Winiarski, Jerzy (Dydaktyka Polonistyczna, 2015)
The article discusses the questions of poetics and philosophy in Bogdan Loebl’s poetry comparing two poems: Dopóki bolisz [Until You Hurt] by the aforementioned author and Leopold Staff’s sonnet Kowal [Blacksmith]. The confrontation of the two poems is designed as a ready-to-use lesson plan, especially helpful for students attending the last year of high school in view of the final exam. The article includes the contexts of both genesis of the two discussed poems and functions of cultural discourse.